2022
DOI: 10.1111/nph.18118
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of specialist and generalist plant–microbial interactions as drivers of plant–soil feedback

Abstract: Introduction: host specificity as the key assumption in plant-soil feedback research 1930 II. How prevalent is host specificity in belowground plant-microbial associations? 1932 III. Redefining specificity in belowground plant-microbial associations 1933 IV. Plant-pathogen interactions as drivers of PSF 1933 V. Mutualistic interactions as drivers of PSF 1935 VI. Soil microbial decomposers as drivers of PSF 1936 VII. Synthesis: mapping plant-microbial interactions and resulting PSFs onto major axes of variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 159 publications
(278 reference statements)
1
83
0
Order By: Relevance
“…Such variability in the relative abundance possibly occurs because such OTUs are differentially supported by specific combination of scion/rootstock genotypes. As suggested by Semchenko et al (2022), the identification of the factors that promote the plant association with microbial specialists and/or generalists will advance our understanding of the mechanisms regulating plant-soil feedback and of the ways plant-microbiome contributes to plant performances.…”
Section: Discussionmentioning
confidence: 99%
“…Such variability in the relative abundance possibly occurs because such OTUs are differentially supported by specific combination of scion/rootstock genotypes. As suggested by Semchenko et al (2022), the identification of the factors that promote the plant association with microbial specialists and/or generalists will advance our understanding of the mechanisms regulating plant-soil feedback and of the ways plant-microbiome contributes to plant performances.…”
Section: Discussionmentioning
confidence: 99%
“…For example: Semchenko et al . (2022) convincingly challenge the assumption that microbially‐mediated plant–soil feedback is driven by specialism in plant–microbial interactions; and Weigelt et al . (2021) use belowground plant traits to assess aboveground–belowground trait coordination and identify an orthogonal ‘collaboration’ gradient, that is, the capability of outsourcing nutrient acquisition to collaborative fungal partners, within the range of global plant form and function.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yea...mentioning
confidence: 99%
“…These, in exchange for a number of products assimilated by photosynthesis [14], protects against pathogens [15][16][17], limits abiotic stresses [18][19][20][21][22] and restricts the heavy metals of the host species [23][24][25]. In addition, mycorrhizal fungi interconnect with the grassland species through a network of hyphae [26], thus intervening in the dynamics of the plant community [27,28]. It has been shown that the involvement of plants in a symbiotic partnership with mycorrhizal fungi can lead to the dominance of some species, as well as to the exclusion of other plants [29][30][31].…”
Section: Introductionmentioning
confidence: 99%